Low‐protein diet for conservative management of chronic kidney disease: a systematic review and meta‐analysis of controlled trials. Issue 2 (2nd November 2017) - Rhee, Connie M.; Ahmadi, Seyed‐Foad; Kovesdy, Csaba P.; Kalantar‐Zadeh, Kamyar
Abstract: Background: Recent data pose the question whether conservative management of chronic kidney disease (CKD) by means of a low‐protein diet can be a safe and effective means to avoid or defer transition to dialysis therapy without causing protein‐energy wasting or cachexia. We aimed to systematically review and meta‐analyse the controlled clinical trials with adequate participants in each trial, providing rigorous contemporary evidence of the impact of a low‐protein diet in the management of uraemia and its complications in patients with CKD. Methods: We searched MEDLINE (PubMed) and other sources for controlled trials on CKD to compare clinical management of CKD patients under various levels of dietary protein intake or to compare restricted protein intake with other interventions. Studies with similar patients, interventions, and outcomes were included in the meta‐analyses. Results: We identified 16 controlled trials of low‐protein diet in CKD that met the stringent qualification criteria including having 30 or more participants. Compared with diets with protein intake of >0.8 g/kg/day, diets with restricted protein intake (<0.8 g/kg/day) were associated with higher serum bicarbonate levels, lower phosphorus levels, lower azotemia, lower rates of progression to end‐stage renal disease, and a trend towards lower rates of all‐cause death. In addition, very‐low‐protein diets (protein intake <0.4 g/kg/day) were associated with greater preservation of kidney function and reduction in the rate of progression to end‐stage renal disease. Safety and adherence to a low‐protein diet was not inferior to a normal protein diet, and there was no difference in the rate of malnutrition or protein‐energy wasting. Conclusions: In this pooled analysis of moderate‐size controlled trials, a low‐protein diet appears to enhance the conservative management of non‐dialysis‐dependent CKD and may be considered as a potential option for CKD patients who wish to avoid or defer dialysis initiation and to slow down the progression of CKD, while the risk of protein‐energy wasting and cachexia remains minimal.